PENGARUH ISLAMIC CORPORATE GOVERNANCE DAN INTERNAL CONTROL TERHADAP INDIKASI TERJADINYA FRAUD PADA BANK UMUM SYARIAH DI INDONESIA - Rahmayani Rahmayani; Rahmawaty Rahmawaty (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The purpose of this study is to examine the effect of independent variables on fraud of Indonesian Islamic banks in the period of 2011-2015. Independent variables that used in this study are Islamic corporate governance with the execution of duties and responsible of Shariah Supervisory Board and the execution of duties and responsible of management as an indicator and internal control. By using purposive sampling method, from 12 Islamic banks in Indonesian, 9 Islamic banks are choosen as the samples in this study. The type of data used in this study aresecondary data which is good corporate governance statement. Collecting data technique used in this study is documentary. Data are analyzed by statistical analysis using a multiple regression analysis and are processed by IBM Statistical Package for Social Science (SPSS) 23th version program. The results of this study show that 6,1% dependent variable or fraud can be explained by the three of independent variables. Simultaneously the three of independent variables have no effect on fraud. Partially the execution of duties and responsible of Shariah Supervisory Board and the execution of duties and responsible of management and internal controlhave no effect on fraud.